2017
DOI: 10.1021/jacs.7b01124
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled Synthesis of Kalihinol C

Abstract: We report a concise chemical synthesis of kalihinol C via a possible biosynthetic intermediate, ‘protokalihinol,’ which was targeted as a scaffold en route to antiplasmodial analogs. High stereocontrol of the kalihinol framework relies on a heterodendralene cascade to establish the target stereotetrad. Common problems of regio- and chemoselectivity encountered in the kalihinol class are explained and solved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Additionally, use of a chiral tethered ligand in allene 8 could enable stereocontrol of the newly formed stereocenter of 10 . Overall, we envisioned that this methodology could be a valuable entry into chiral lactone 15 or tetrahydrofuran 16 containing natural products (Scheme 1) through lactol 11 obtained by hydrolysis of the enol or enamine functionality of 10 . Herein, we report our findings on the development of a diastereoselective copper-catalyzed reductive coupling of a chiral allenamide with ketones to access the linear isomer ( 10 ) of product.…”
mentioning
confidence: 99%
“…Additionally, use of a chiral tethered ligand in allene 8 could enable stereocontrol of the newly formed stereocenter of 10 . Overall, we envisioned that this methodology could be a valuable entry into chiral lactone 15 or tetrahydrofuran 16 containing natural products (Scheme 1) through lactol 11 obtained by hydrolysis of the enol or enamine functionality of 10 . Herein, we report our findings on the development of a diastereoselective copper-catalyzed reductive coupling of a chiral allenamide with ketones to access the linear isomer ( 10 ) of product.…”
mentioning
confidence: 99%
“…As a general approach to the polycarbocyclic ICTs, Shenvi’s dendralene-based strategy is exceptionally direct, and the method for isonitrile installation is potentially broadly impactful. As this manuscript was in preparation, Reiher and Shenvi showed that this creative synthesis design could also be applied to the kalihinol problem (Scheme ), in this case using a heterodendralene ( 50 ) . In this case, after initial regular electron-demand cycloaddition of the Rawal-type diene and hydrolysis of the vinylogous hemiaminal that results, the α,β-unsaturated carboxylic acid reacts via an IMHDA cycloaddition, thus controlling the configuration of the challenging stereotetrad.…”
Section: Three Approaches Used To Access Multiple Different Ict Targetsmentioning
confidence: 99%
“…As this manuscript was in preparation, Reiher and Shenvi showed that this creative synthesis design could also be applied to the kalihinol problem (Scheme 9), in this case using a heterodendralene (50). 25 In this case, after initial regular electron-demand cycloaddition of the Rawal-type diene 26 and hydrolysis of the vinylogous hemiaminal that results, the α,βunsaturated carboxylic acid reacts via an IMHDA cycloaddition, thus controlling the configuration of the challenging stereotetrad. Most notably, this approach very cleverly solves the C7− C11 stereochemical relationship, and permits rapid access to advanced intermediate 53 after Krapcho-like dephosphonyla- tion, nucleophilic methylation at C10, and ester hydrolysis/ decarboxylation.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 6 Oxygen-containing FGs, such as OH, sulfonyloxy groups (for example, OMs and OTs) and trifluoroacetoxyl groups (OTFA), are generally regarded as common transformation precursors for derivatizations. 7 Site-selective C(sp 3 )–H bond oxidation is a straightforward yet valuable synthetic method to install such groups ( Scheme 1 , path a). 8 However, direct C–H bond oxidation usually suffers from poor selectivity when multiple electronically and sterically similar C–H bonds are present in one molecule.…”
Section: Introductionmentioning
confidence: 99%